The Perspective of University of Primorska Graduates on Lifelong Learning and Education (Journal of Universal Excellence, 2026)
Research Question (RQ): How can educational institutions support the lifelong learning of graduates and what key competences and skills do they desire and contribute to their success in the labour market?Purpose: The aim of the research is to investigate graduates' views on lifelong learning and education during their working life.Method: The qualitative method was used for the study. The data was collected from a selected sample of graduates from the University of Primorska through semi-structured interviews in two focus groups. The data was analyzed using the content analysis method.Results: Four themes were developed using the analysis method: (1) the role of lifelong learning, (2) the development of competences, (3) support from educational institutions and (4) challenges and opportunities. The results of the study show that the graduates of the University of Primorska are highly motivated to pursue lifelong learning, especially to acquire specific competences such as digital and green skills and soft skills. It was found that educational institutions play a key role in supporting graduates in their continuing education, but that the programmes and forms of education need to be adapted to make them more flexible and practice oriented.Organization: The study underlines the need for closer cooperation between educational institutions and companies to offer tailor-made educational programmes that enable graduates to better match the skills they have acquired with the needs of the labour market. It provides guidelines for adapting lifelong learning courses to the needs of graduates.Society: Research helps to raise awareness of the importance of lifelong learning for individuals and society. It emphasizes the need to develop skills that are central to sustainable development and that can contribute to greater social responsibility and environmental awareness in society in the long term. It promotes the integration of environmentally friendly practices and digital skills that have a positive impact on society and the environment.Originality: The research provides insights into the specific needs of graduates in the field of lifelong learning and offers insights into the specific challenges and opportunities they face. The originality of the research is demonstrated by the focus on adapting educational programmes to today's labour market demands and integrating sustainable practices into curricula.Limitations/Future Research: Limitations of the study include its limited geographical scope as it focuses on the graduates of a single university. It is suggested that further research be conducted to include a larger and more diverse population and to conduct longitudinal studies to track the development of competences over time.
Keywords: lifelong learning; education; graduates; competences; higher education institutions